How to foster the commitment level of managers? Exploring the role of moderators on the relationship between job satisfaction and organizational commitment: A study of educational managers in Vietnam - Huynh, Tho H. P.; Bui, Thong Quang; Nguyen, Phuong N. D. (Frontiers in Education, 2023)
Organizational commitment is a perennial concern. Numerous studies have been conducted to figure out how to strengthen the commitment of employees to the organization. Many of them examined the moderating factors that influence the link between job satisfaction and organizational commitment. However, the majority of past research has focused on the private and corporate sectors. Further, some management personnel opts to quit the firm while still being content with their existing position. Therefore, this study aims to investigate the role of moderators in the relationship between job satisfaction and organizational commitment by applying the purposive sampling method to conduct the data survey of 402 managers in Ho Chi Minh City, Vietnam, who work in the public education sector. By using the PLS-SEM modeling approach with the help of SmartPLS 4 software to examine the research hypotheses, the results reveal that organizational commitment is positively affected by job satisfaction and work engagement. At the same time, managers with high person-organization fit and fun at work will have higher levels of organizational commitment in situations of high satisfaction in their jobs. Conversely, high role stress will dampen the levels of organizational commitment in situations of high job satisfaction. The results offered some managerial implications to strengthen the commitment to the organization of the managers in the educational sector. This research also stressed some limitations and suggested opportunities for future investigation.